Comparison of Standard and Newer Balance Tests in Recreational Alpine Skiers and Ski Novices - Vjekoslav Cigrovski; Ivica Franjko; Tomislav Rupčić; Marijo Baković; Andro Matković (Montenegrin Sports Academy, 2017)
Alpine skiers should physically prepare for skiing due to the specific body movements it requires. As balance is essential for the success of competitive alpine skiers, we investigated its importance during preparation for alpine skiing in recreational skiers. We included 24 male participants; twelve recreational skiers just after 10 days of alpine skiing, and twelve alpine ski novices. All participants were tested with two balance tests (BAL40 and GYKO). Participants of the two groups did not differ significantly in the results of the BAL40 standard balance test. In contrast, we found significant differences in four out of six variables measured with the GYKO test performed on BOSU trainer during the two-feet stand. Participants specifically differed in the variables overall average body tilt (p=0.02), overall average deviation of body tilt (p=0.00), overall medio-lateral average body tilt (p=0.01), and overall medio-lateral average deviation of body tilt (0.00). Average results were lower for participants of the group of recreational skiers than for participants of the novice alpine ski group, suggesting that balance is important for recreational skiers, either as an acquired trait during skiing, or the result of conditioning training in the preparation period for skiing. According to the results, we would advise recreational skiers as well as people planning to be involved in alpine skiing as a new recreational activity to include balance exercises in the preparation period.